2019
DOI: 10.1183/13993003.01335-2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of asthma exacerbation during pregnancy in women with asthma: a population-based cohort study

Abstract: The association between asthma exacerbation during pregnancy and adverse maternal and child health outcomes have not been investigated appropriately. Our objective was to determine the short- and long-term intergenerational effect of asthma exacerbation in pregnant women with asthma.A population cohort study was conducted using data from the Ontario asthma surveillance system and population-level health administrative data. Asthma exacerbation in pregnant women with asthma was defined as at least one of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…This supports two studies reporting increased risk of preterm birth for women experiencing an asthma exacerbation during pregnancy [9] or women with poorly-controlled asthma in the 90 days prior to delivery [11]. These findings may explain in part the observations for the reduction in birth weight.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This supports two studies reporting increased risk of preterm birth for women experiencing an asthma exacerbation during pregnancy [9] or women with poorly-controlled asthma in the 90 days prior to delivery [11]. These findings may explain in part the observations for the reduction in birth weight.…”
Section: Discussionsupporting
confidence: 88%
“…-fold increased risk of having a an infant born SGA. This supports other studies which found increased risk of SGA among those with poorly-controlled asthma vs well-controlled asthma in the 90 days prior to delivery (aRR 1.15, 95%CI 1.03-1.29)[8,9]. Among these women, having an asthma exacerbation during pregnancy may worsen the hypoxic intrauterine environment compared to women with milder asthma, resulting in the increased risk of SGA.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…A recent welldesigned Canadian study of 103,424 singleton pregnancies in women with asthma showed that antepartum asthma attacks were associated with significantly higher rates of congenital malformations; preterm births; low birth weights, early life pneumonia and asthma; pregnancy-induced hypertension; and pre-eclampsia ( Figure 3). 3 Are the effects of pregnancy on asthma truly 'unpredictable'?.…”
Section: Asthma and Pregnancymentioning
confidence: 99%